A theoretical review on the effects of road hump on traffic volume, speed and noise in residential areas - Ahmad Sofi, Siti Syazwani; Kadar Hamsa, Abdul Azeez (Kulliyah of Architecture and Enviromental Design, 2017)
Living environment in residential areas can be disturbed by the over-speeding of vehicles resulting in increased noise level. Extreme speed and noise create aggravation such as sleep disturbance and health problems among the residents, as well as causing physical impacts. Therefore, as a corrective measure, it becomes a trend in the new development of residential areas to install road humps on these residential roads. The proper installation of road humps on the residential roads is an alternative method to enforce speed limits, thereby preventing high traffic volume and noise in residential areas. Various literature had depicted that road humps increase the noise level due to the sudden braking of vehicles when approaching humps albeit the speed reduces. This paper deliberated the effectiveness of road humps on traffic volume, speed and noise in residential areas from the literature. This paper also discussed the effects of the design profiles of road hump on the change in speed of vehicles, traffic volume and noise level.